2020
DOI: 10.18332/tid/118721
|View full text |Cite
|
Sign up to set email alerts
|

School-type differences in e-cigarette use and its correlates among Chinese adolescents

Abstract: INTRODUCTION Studies examining e-cigarette use among adolescents in Shanghai, China, have focused largely on middle school students. Given the vast differences between vocational and traditional schools, we aimed to explore school-type differences in e-cigarette use and correlates among adolescents in Shanghai. METHODS The study was conducted in September 2017 through multistage and stratified cluster random sampling, which consisted of 10699 adolescents aged 13-17 years attending traditional and vocational sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…According to the results, the trend of lifetime and current prevalence of e-cigarettes vaping in adolescents has been increasing, for example, the lifetime prevalence rate in the UK has increased from 22% in 2014 to 25% in 2016 [161], also the current prevalence rate in the United States has increased rapidly from 1.5% in 2011 to 20.8% in 2018 [162]. In various studies, a positive relationship has been found between the amounts of monthly allowance given by parents to their adolescent children, so as much as the amount of money is higher, the probability of e-cigarettes vaping is also higher by children [144,[163][164][165] and this factor could have been a reason to increase e-cigarettes vaping. Another reason for increasing the prevalence of e-cigarettes vaping could be the use of e-cigarettes to quitting conventional cigarette by adolescents.…”
Section: Prevalence In Adolescent's and School Studentsmentioning
confidence: 99%
“…According to the results, the trend of lifetime and current prevalence of e-cigarettes vaping in adolescents has been increasing, for example, the lifetime prevalence rate in the UK has increased from 22% in 2014 to 25% in 2016 [161], also the current prevalence rate in the United States has increased rapidly from 1.5% in 2011 to 20.8% in 2018 [162]. In various studies, a positive relationship has been found between the amounts of monthly allowance given by parents to their adolescent children, so as much as the amount of money is higher, the probability of e-cigarettes vaping is also higher by children [144,[163][164][165] and this factor could have been a reason to increase e-cigarettes vaping. Another reason for increasing the prevalence of e-cigarettes vaping could be the use of e-cigarettes to quitting conventional cigarette by adolescents.…”
Section: Prevalence In Adolescent's and School Studentsmentioning
confidence: 99%
“…According to the National Health Examination Survey (NHES), from 2019 to 2020, 2.9% of Thais aged 10–19 years currently used e-cigarettes 27 . A similar finding was reported in the study about students’ e-cigarette use in different vocational education schemes 28 . This finding of a higher percentage of vocational students using e-cigarettes could be because the vocational education program aims to enhance students’ vocational skills.…”
Section: Discussionsupporting
confidence: 89%
“…Ever EC use increased from 1.8 to 7.1% in never smoking adolescents over 17 months in 2014–15 in Argentina, and 6.5% of Mexican adolescents had ever used ECs in 2016 [ 18 , 19 ]. China had one of the highest smoking rates in the world (52.1% current smoking in males in 2015), [ 20 ] but the prevalence of EC use was relatively low, with 3.1% adults in 2015 and 5.2% adolescents in 2017 being ever users [ 20 , 21 ]. EC awareness in urban adult smokers increased from 29% in 2009 to 60% in 2015, and 70.6% middle and high school students were aware of ECs in 2017 in China [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%